EFEKTIVITAS TERAPI ICE MASSAGE DAN BACK MASSAGE TERHADAP PERUBAHAN INTENSITAS NYERI PADA PASIEN LOW BACK PAIN DI RUMAH SAKIT GRANDMED LUBUK PAKAM TAHUN 2020 - Kardina Hayati; Tati Devi (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2020)
Abstract Low back pain is one of the causes of musculoskeletal due to poor activity the emergence of aches, rheumatic pain, aching. Pain management can be overcome by non-pharmacological therapy using back and ice massage. The purpose of this study was to looked for effectiveness of message ice therapy and back massage for changes in pain intensity in low back pain patients at Grandmed Lubuk Pakam Hospital. The research method used was pre-experiment with a one group pre-test post test design model, the sample consisted of 30 samples taken by purposive sampling. Analysis of the data used is the Paired Sample t-test. The results showed there is an effectiveness of Ice Massage therapy and Back Massage therapy at the level of pain intensity in Low Back Pain patients. The result Based on the results of the statistical test, the value of p=0,001â‰¤ É‘ 0,05 for each therapy. Statistical effectiveness test was performed between ice massage and back massage therapy on the level of pain intensity was the most effective back massage therapy to reduce pain intensity with a value of 3,600 and SD (0.516). Cold compresses have several advantages including causing local analgesic effects, reducing inflammation, increasing the threshold for pain receptors and then reducing pain. Back massage can cause a mechanism to close the pain impulse while rubbing the patient's roller gently. The resulting message will stimulate the mechanoreceptor. Expected ice massage and back therapy can be an alternative nursing action in dealing with pain in low back pain patients. Keywords: ice and back massage, low back pain